A Feasibility Study for Determining Ablative Margin with 3D-CEUS-CT/MR Image Fusion after Radiofrequency Ablation of Hepatocellular Carcinoma - Zhong-Zhen, S.; Kai, L.; Rong-Qin, Z.; Er-Jiao, X.; Ting, Z.; Ao-Hua, Z.; Shu-Fang, Y.; Xu-Qi, H. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: To explore the feasibility and value of 3D-CEUS-CT/MR image fusion in evaluating ablative margin (AM) after radiofrequency ablation of hepatocellular carcinoma.Methods and materials: There were 49 HCC in 41 patients enrolled in our prospective study. The AM were evaluated with 3D-CEUS-CT/MR image fusion, the results were divided into two groups: in group A, the tumor was completely ablated with a 5 mm AM; in group B, the tumor was completely ablated, but a 5 mm AM was not obtained. The time used in US-CT/MR image fusion and 3 D image post-processing, the technical success rate of 3D-CEUS-CT/MR image fusion and the relation between LTP and AM were observed.Results: The time taken for US-CT/MR image fusion and 3 D image post-processing was 9.2 ± 2.1 min (6 – 12 min), 14.6 ± 2.6 min (9 – 20 min), respectively. The technical success rate of 3D-CEUS-CT/MR image fusion was 81.6 % (40/49). 27 HCC had sufficient AM (group A) and 13 HCC had insufficient AM (group B). The LTP rates in groups A and B were 0/27 and 4/13, respectively. There was a significant difference between groups A and B (P = 0.002). There was a significant negative correlation between LTP and AM (r = –1.000, P< 0.001), and the locations of LTP and insufficient AM were concordant.Conclusions: The results suggest that 3D-CEUS-CT/MR image fusion is feasible and useful in evaluating the AM after HCC ablation.
Keywords: 3-D ultrasound; radiofrequency (RF) ablation; treatment effects; tumor; MR-imaging